Basic English for computing - Glendinning, Eric H.; McEwan, John. (Oxford : Oxford University Press, 1999)
Everyday uses of computers. Types of computer. Parts of a computer. Keyboard and mouse. Interview: student. Input devices. Output devices. Storage devices. Graphical user interface. Interview: computing support assistant. Networks. Communications...
Keywords: English language; Foreign speakers; Computer science -- Terminology; English language -- Sound recordings for foreign speakers; Computers -- Terminology